Encyclopedia of the solar system - Spohn, T. (Tilman); Breuer, Doris, 1965-; Johnson, T. V. (Torrence V.) (Amsterdam : Elsevier, 2014)
"This book is filled with the knowledge about our solar system that resulted from all this exploration, whether by spacecraft or by telescopes both in space and earth-bound. All of this new knowledge is based on discoveries made in the interim by scientist-explorers who have followed their inborn human imperative to explore and to understand. Many old mysteries, misunderstandings, and fears that existed 50 years ago about what lay beyond the Earth have been eliminated. We now know the major features of the landscape in our cosmic backyard and can look forward to the adventure, excitement, and new knowledge that will result from more in-depth exploration by today's spacecraft, such as those actually exploring the surface of these faraway places, including the Huygens Titan lander and the Mars Exploration rovers, doing things that were unimaginable before the Space Age began. The Encyclopedia of the Solar System is filled with images, illustrations, and charts to aid in understanding. Every object in the solar system is covered by at least one chapter. Other chapters are devoted to the relationships among the objects in the solar system and with the galaxy beyond. The processes that operate on solar system objects, in their atmospheres, on their surfaces, in their interiors, and interactions with space itself are all described in detail. There are chapters on how we explore and learn about the solar system and about the investigations used to make new discoveries. And there are chapters on the history of solar system exploration and the missions that have carried out this enterprise. All written by an international set of world-class scientists using rigorous yet easy-to-understand prose"--Provided by publisher.
Part VII: Giant planets and their satellites. Atmospheres of the giant planets ; Interiors of the giant planets ; Planetary satellites ; Io: The volcanic moon ; Europa ; Ganymede and Callisto ; Titan ; Enceladus ; Triton ; Planetary rings -- Part VIII: Beyond the planets. Pluto ; Kuiper Belt: dynamics ; Kuiper Belt objects: physical studies ; Extrasolar planets -- Part IX: Exploring the solar system. Strategies of modern solar system exploration ; A history of solar system studies ; X-rays in the solar system ; The solar system at ultraviolet wavelengths ; Infrared views of the solar system from space ; New generation ground-based optical/infrared telescopes ; The solar system at radio wavelengths ; Planetary radar ; Remote sensing of chemical elements using nuclear spectroscopy ; Probing the interiors of planets with geophysical tools ; Planetary exploration missions ; Exploration and analysis of planetary shape and topography using stereophotogrammetry.
Includes bibliographical references and index.
Print version record.
Keywords: Solar system -- Encyclopedias; SCIENCE -- Astronomy; Solar system; Astronomy & Astrophysics; Physical Sciences & Mathematics; Astrophysics; Solar System -- Encyclopedias; Electronic book; Electronic books; Ebook; Encyclopedias; Electronic books